2020
DOI: 10.1128/msphere.00538-20
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling Suggests T Cells Cluster around Neurons Injected with Toxoplasma gondii Proteins

Abstract: Toxoplasma gondii’s tropism for and persistence in the central nervous system (CNS) underlies the symptomatic disease that T. gondii causes in humans. Our recent work has shown that neurons are the primary CNS cell with which Toxoplasma interacts and which it infects in vivo. This predilection for neurons suggests that T. gondii’s persistence in the CNS depends specifically upon parasite manipulation of the host neurons. Yet, most work on T. gondii-host cell interactions has been done in vitro and in nonneuron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…The inflammatory signature of mice infected with ΔROCY1 and ΔBFD1 parasites was also significantly different as determined using gene set enrichment analysis (GSEA; (Subramanian et al ., 2005)), where pathways like “HALLMARK INFLAMMATORY RESPONSE” and “HALLMARK IL2 STAT5” were similarly and significantly enriched based on a false-discovery rate of 0.05 (Figure S5D). We then used the informatics tool Cibersort (Newman et al ., 2019) which can be used to infer percentages of different cell populations in bulk RNAseq data and that has recently been applied to brain RNAseq data from T. gondii -infected mice (Merritt et al ., 2020). Given our interest in the inflammatory profile of mice infected with wild type and cyst-deficient T. gondii (ΔROCY1 and ΔBFD1), we used the precomputed “LM22” as the signature gene file and used it to estimate the relative proportions of 22 immune cell types using our brain RNAseq data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The inflammatory signature of mice infected with ΔROCY1 and ΔBFD1 parasites was also significantly different as determined using gene set enrichment analysis (GSEA; (Subramanian et al ., 2005)), where pathways like “HALLMARK INFLAMMATORY RESPONSE” and “HALLMARK IL2 STAT5” were similarly and significantly enriched based on a false-discovery rate of 0.05 (Figure S5D). We then used the informatics tool Cibersort (Newman et al ., 2019) which can be used to infer percentages of different cell populations in bulk RNAseq data and that has recently been applied to brain RNAseq data from T. gondii -infected mice (Merritt et al ., 2020). Given our interest in the inflammatory profile of mice infected with wild type and cyst-deficient T. gondii (ΔROCY1 and ΔBFD1), we used the precomputed “LM22” as the signature gene file and used it to estimate the relative proportions of 22 immune cell types using our brain RNAseq data.…”
Section: Resultsmentioning
confidence: 99%
“…We then used the informatics tool Cibersort (Newman et al, 2019) which can be used to infer percentages of different cell populations in bulk RNAseq data and that has recently been applied to brain RNAseq data from T. gondii-infected mice (Merritt et al, 2020). Given our interest in the inflammatory profile of mice infected with wild type and cyst-deficient T. gondii (ΔROCY1 and ΔBFD1), we used the precomputed "LM22" as the signature gene file and used it to estimate the relative proportions of 22 immune cell types using our brain RNAseq data.…”
Section: Rocy1 Is Necessary For Brain Tissue Cyst Formation During Mu...mentioning
confidence: 99%
See 1 more Smart Citation
“…found that CCL2 expression is upregulated in regions of the brain cells without significant interaction with T . gondii , but was found within 120 μm of a parasite-interacted cell [ 49 ]. In the periphery, innate immune recognition of T .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also clear that direct invasion of host cells in the brain by T. gondii is not required for CCL2 production. Merritt et al found that CCL2 expression is upregulated in regions of the brain cells without significant interaction with T. gondii, but was found within 120 μm of a parasite-interacted cell [49]. In the periphery, innate immune recognition of T. gondii profilin by TLR11/12 induces CCL2 production and monocyte recruitment [33].…”
Section: Plos Pathogensmentioning
confidence: 99%